Analisis Finansial Usaha Peternakan Babi (Studi Kasus Peternakan Babi UD Karang di Desa Jagapati, Kecamatan Abiansemal,Kabupaten Badung) - KUEAIN, YOSSY ACHRIBSONE; SUAMBA, I KETUT; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017), 2017)
Business Financial Analysis on Piggery (A Case Study of Piggery of UD Karang at Jagapati Village, Sub-District of Abiansemal, Badung) Pigs is one commodity of livestock meat producer. Pigs have qualities and abilitiesthat benefit namelyit hasfaster growth rate and also a higher number of piglets perbirth. Pork demand has improved in the area of Bali that can provide businessopportunities to UD Karang to develop a piggery by raising pigs to be fattening.Piggery business needs to do a financial analysis to determine the success of itsbusiness. The purpose of this study was to determine the feasibility of a piggery interms of financial aspects and the obstacles being faced. This research was conductedon a piggery of UD. Karang located in the village of Jagapati, AbiansemalSubdistrict of Badung Regency. The analytical methods used were quantitative andqualitative methods. The study results and the conclusions showed that the piggery ofUD Karang is financially feasible with NPV value of Rp 452, 693. 850, thenet valueof B/C of 1.3 and the IRR of 74.62%. The obstacles faced by the piggery of UDKarang namely respiratory disease in swine livestock, price fluctuations, andenvironmental pollution. Suggestions given to UD Karang that it should work withthe Department of Animal Husbandry and Animal Health, add good quality feed soas to meet the nutritional needs of the animals, and the pig manure should befermentedto be utilized as biogas.
Keywords: pigs; financial analysis; obstacles